Association between plasma transfusions and clinical outcome in critically ill children: a prospective observational study. Issue 4 (7th January 2013) - Karam, O.; Lacroix, J.; Robitaille, N.; Rimensberger, P. C.; Tucci, M.
<x xml:space="preserve">Abstract</x> Background and Objectives Plasma transfusions are commonly used in adult and paediatric intensive care units. Recent data suggest an association between plasma transfusions and worse clinical outcome in adult trauma patients. To date, no prospective paediatric study has addressed this issue. Our objective was to prospectively analyse the association between plasma transfusions and clinical outcome of critically ill children. Materials and Methods Prospective, observational and single centre study that includes all consecutive admissions to a tertiary level multidisciplinary paediatric critical care unit over a 1‐year period. The primary outcome measure was the incidence after transfusion of new or progressive multiple organ dysfunction syndrome. Secondary outcome measures included nosocomial infections, intensive care unit length of stay and 28‐day mortality. Odds ratios were adjusted for weight, severity of illness, coagulopathy, plasma transfusions prior to admission, need for extracorporeal life support and transfusion of other labile blood products. Results A total of 831 patients were enrolled, among which 94 (11%) received at least one plasma transfusion. In the latter group of patients, the adjusted odds ratio for an increased incidence of new or progressive multiple organ dysfunction syndrome was 3·2 (P = 0·002). There was also a significant difference in the occurrence of nosocomial infections and intensive care unit length of stay, but no significant difference in the 28‐day mortality. Conclusions In critically ill children, plasma transfusions seem to be independently associated with an increased occurrence of new or progressive multiple organ dysfunction syndrome, nosocomial infections and prolonged length of stay.